The Effect of Entrepreneurial Knowledge and Entrepreneurship Motivation on Entrepreneurial Intention Mediated by the Utilization of Media Social - Ananda Anjani Alam; Henry Eryanto; Nadya Fadillah (Research Trend in Technology and Management, 2023)
This study aims to determine the effect of entrepreneurial knowledge and entrepreneurial motivation on entrepreneurial intentions mediated by the use of social media in students of the Faculty of Economics, State University of Jakarta. This research uses quantitative research methods and uses survey methods. The sampling technique used the Proportional Random Sampling Technique with a sample of 198 students. The data analysis technique used in this study uses Structural Equation Modeling Partial Least Square (SEM-PLS) which is calculated using Smart PLS software version 3.3.9. The results of this study indicate that entrepreneurial knowledge has a significant effect on entrepreneurial motivation, entrepreneurial knowledge has a significant effect on entrepreneurial intentions, entrepreneurial motivation has a significant effect on entrepreneurial intentions, the use of social media has a significant effect on entrepreneurial intentions, entrepreneurial knowledge has a significant effect on entrepreneurial intentions mediated by the use of social media. , and entrepreneurial motivation has a significant effect on entrepreneurial intentions mediated by the use of social media.